2021
DOI: 10.1080/09712119.2021.1895173
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of some meat and liver quality traits in Muscovy and Pekin ducks

Abstract: The objective of the study was to compare Muscovy and Pekin ducks for proximate analysis, colour attributes, tenderness, meat microstructure, and content of some minerals in meat and liver. The material of the study was sexed 51 Muscovy ducks and 47 Pekin ducks. At the end of the rearing period, 40 birds were selected for dissection. Duck genotype influenced the content of water, protein, fat, collagen, zinc, iron, haematin, and redness, chroma, hue angle, WB shear force, muscle fibre diameter and density of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
1
5
1
Order By: Relevance
“…Of note, in the present experiment slaughter age had large effects on color and tenderness of the breast muscle. A greater force had to be applied to cut breast muscles in older birds than in younger ones, which is consistent with previous findings in broilers ( Chen et al., 2007 ), geese ( Uhlirova et al., 2018 ), and ducks ( Kokoszyński et al., 2021 ; Muhlisin et al., 2013 ). This is probably associated with the lower muscle fiber diameter of lighter ducks.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Of note, in the present experiment slaughter age had large effects on color and tenderness of the breast muscle. A greater force had to be applied to cut breast muscles in older birds than in younger ones, which is consistent with previous findings in broilers ( Chen et al., 2007 ), geese ( Uhlirova et al., 2018 ), and ducks ( Kokoszyński et al., 2021 ; Muhlisin et al., 2013 ). This is probably associated with the lower muscle fiber diameter of lighter ducks.…”
Section: Discussionsupporting
confidence: 91%
“…Taking meat color into account, the change in color indicated by a lower L∗, and a higher a∗ of breast muscle as the birds matured could be related to the development of the muscle tissue, i.e., increases in cross-sectional area of muscle fiber or increases in collagen content and cross-linking with age ( Dransfield and Sosnicki, 1999 ). In addition, the darker color of meat in older ducks probably resulted from a significantly higher content of haem pigments accompanied by better blood supply to the muscles ( Kokoszyński et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research has demonstrated that supplementing feed with probiotics considerably raised the protein content of meat while reduced the fat content of broiler meat, which concur with the findings of the current inquiry ( Chen et al, 2014 ). Current research has also confirmed that the probiotics' effects were evident in the treated ducks' higher levels of protein and decreased levels of fat in their meat ( Kokoszyński et al, 2021 ).…”
Section: Discussionmentioning
confidence: 81%
“…It can be assessed instrumentally or organoleptically. Meat tenderness is determined by the type and diameter of the muscle fibres, the proportion of perimysium and epimysium, the rate of proteolytic changes post mortem, the water holding capacity, and the ultimate pH [ 22 , 23 , 24 , 25 ]. The meat of young broiler-type commercial birds is more tender than that of older birds due to the smaller diameter of the muscle fibres and the better solubility of the collagen.…”
Section: Introductionmentioning
confidence: 99%